Mongolia : 2013 Article IV Consultation-Staff Report; Press Release and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report, 2014)
This 2013 Article IV Consultation highlights economic developments and policies of Mongolia between 2003 and 2013. The resulting balance-of-payments (BOP) pressures have been compounded by negative shocks to foreign direct investment (FDI) and coal exports. The IMF report analyzes that various banking sector vulnerabilities and weaknesses in the business climate need to be addressed to steady the progress of the economy. Launch of new investment law is important to be introduced by the government to improve the business climate and encourage FDI inflows.